A Case of Diltiazem-Induced Pustular Rash in an 83-Year-Old Female - Ayrton I. Bangolo; Karen Yelton-Torres; Atharv Mahajan; Vrusha Patel; Laiba Sajjad; Prince Ofori Ansong; Monisha Kashyap; Umesh Batura; Madhavi Ravulapalli; Ayodya Perera; Simcha Weissman (Case Reports in Dermatological Medicine)
Acute generalized exanthematous pustulosis (AGEP) is a rare, acute skin eruption characterized by the development of numerous nonfollicular sterile pustules. Most cases are caused by drug reactions, among which Diltiazem has been incriminated. Herein, we present an 83-year-old female who presented for evaluation of generalized skin rash 3 days after initiation of Diltiazem. She was eventually diagnosed with AGEP, Diltiazem was discontinued, and systemic steroids were administered with the resolution of symptoms. This case report has the objective of encouraging clinicians to include AGEP in the differential diagnosis of skin eruption following the initiation of Diltiazem.